Seroprevalence of Aspergillus IgG and disease prevalence of chronic pulmonary aspergillosis in a country with intermediate burden of tuberculosis: a prospective observational study. (August 2020) - Lee, M.-R.; Huang, H.-L.; Chen, L.-C.; Yang, H.-C.; Ko, J.-C.; Cheng, M.-H.; Chong, I.-W.; Lee, L.-N.; Wang, J.-Y.; Dimopoulos, G.
Abstract: Objectives: Chronic pulmonary aspergillosis (CPA) is an emerging global disease with tuberculosis (TB) being the most important risk factor. Epidemiologic data on the seroprevalence of Aspergillus IgG and prevalence of CPA in different areas, especially in country with intermediate burden of TB, are lacking. Methods: We prospectively recruited healthy volunteers, TB close contacts, active TB patients and participants with old pulmonary TB in Taiwan during 2012–2019. We measured serum Aspergillus fumigatus and niger -specific IgG levels and assessed if the participants were having CPA. Results: A total of 1242 participants (including 200 healthy volunteers, 326 TB close contacts, 524 active TB patients and 192 old TB cases) were recruited. Using 27 mgA/L (milligrams of antigen-specific antibodies per liter) as cut-off level, the seropositive rate of A. fumigatus -specific IgG was 33.0% (66/200), 37.7% (123/326), 26.5% (139/524) and 43.2% (83/192) among the four groups, respectively. In multivariate logistic regression, pulmonary cavitation (OR 1.73; 95% CI 1.07–2.80), female sex (OR 1.49; 95% CI 1.14–1.95), old TB (OR 1.59; 1.05–2.42) were independent risk factors for Aspergillus IgG positivity. One (0.2%) active TB patient and four (2.1%) old TB patients developed CPA. Correlation between A. fumigatus and A. niger -specific IgG was high (Spearman correlation coefficient: 0.942). Discussion: Geographic variation in Aspergillus IgG seroprevalence and CPA prevalence exists. A universal cut-off value for Aspergillus IgG may not exist. In areas and populations in which background Aspergillus IgG level is unknown, Aspergillus IgG may be better used as a test of exclusion for CPA using prespecified cut-off level.